Building Trust and Quality of Customer Service Through Customer Satisfaction (Study of Gojek’s Customers in Malang City) - Raga Etsenna Wattimena; Liem Gai Sin (AIBPM Publisher, 2020)
Transportation services are a substantial in people's lives due to its widespread in the community to facilitate their daily activities as working, traveling and others. A leading online ride-hailing company, Gojek, was founded by a Indonesian man, Nadiem Makarim in March 2014. It aims to reduce unemployment in Indonesia and provide solutions to congestion in the capital. Online application-based transportation services have been chosen by the public due to its easiness, more transparent cost calculation, and more satisfying service. Customers do not need to leave the house to order the service since they are highly possible to order it online with their smartphone devices.